IDENTIFIKASI KEJADIAN ASFIKSIA NEONATORUM DI RSIA DIAN PERTIWI KABUPATEN KARANGANYAR - Anggraini, Yeni; Utami, Uji (Jurnal Ilmiah Maternal, 2025)
The indicators used to measure a country's health status are maternal and child mortality rates. Underweight children (28.2%) and asphyxia (25.3%) were the leading causes of child mortality in Indonesia in 2022, followed by birth defects, infections, COVID-19, and tetanus in newborns. Maternal factors, placental factors, and congenital factors are the causes of respiratory disorders in newborns. Neonatal asphyxia is the failure of a baby to breathe spontaneously and regularly immediately after birth. Neonatal asphyxia that is not treated properly will be followed by multiple organ failure. The purpose of this study was to determine the incidence of neonatal asphyxia at the Dian Pertiwi Maternity Hospital in Karanganyar Regency. The research method used was descriptive observational. The population in this study consisted of 192 newborns. The sampling technique used was purposive sampling, where the samples were those who met the inclusion criteria, namely all babies born in 2022 with a diagnosis of neonatal asphyxia. Research results: of the 192 respondents, 86 respondents (44.8%) experienced neonatal asphyxia. Based on parity characteristics, the majority of babies with asphyxia were born to primiparous mothers (44 or 51.2%) and were in the 20–35 age range (69 respondents or 80.2%). The majority of babies were born within the gestational age range of 37–41 weeks (45 or 52.3%), the majority of babies were born with normal weight (76 or 88.4%), and the majority of babies with asphyxia were born with prolonged labor (75 or 87.2%). Conclusion: Respondents who experienced neonatal asphyxia at RSIA Dian Pertiwi in Karanganyar Regency were 86 babies (44.8%).